A Cross-Sectional Study to Determine and Compare the Craniofacial Anthropometric Norms in a Selected Kenyan and Chinese Population. Issue 1 (February 2023) - Sarna, Krishan; Sonigra, Khushboo J.; Ngeow, Wei C.
Background: Craniofacial anthropometry provides essential data for diagnosis and treatment planning, with the norms for many races having been investigated. The results reveal that facial morphometry varies greatly because of geographical, ethnic, and racial variations. This study aims to gather the normative anthropometric data and compare the differences in facial morphometry between the Kenyan population and that of the Chinese.Methods: Four vertical measurements (trichion–nasion, nasion–subnasale, subnasale–gnathion, and superaurale–subaurale) and 6 horizontal measurements (zygion–zygion, exocanthion–endocanthion, endocanthion–endocanthion, pupil-pupil, alare–alare, and chelion–chelion) were obtained manually from subjects with no craniofacial abnormality.Results: A total of 180 participants (90 Kenyans and 90 Chinese) were included. Among the Kenyans, males generally had greater dimensions in comparison to the Kenyan females with the exception of the upper third, lower third, and intercanthal, and interpupillary distances. Among the Chinese, there was a significant difference between the 2 genders with the exception of intercanthal distance. All measurements were greater in Chinese males in comparison to the females. Comparison between races shows that Kenyans had greater vertical measurements with exception of the ear length for both genders. The Chinese males had increased facial width and intercanthal distance, while the Chinese females showed increased intercanthal distance compared to Kenyans. Kenyans exhibited hyperleptoprosopic-type face, while Chinese exhibited mesoprosopic-type face, with none of the 2 groups conforming to the neoclassical canons.Conclusion: Kenyans generally have greater craniofacial measurements versus Chinese, except for the facial width and intercanthal distance for males and interorbital distance for females.